Analyzing redistribution policies : a study using Australian data - Kakwani, Nanak (Cambridge [Cambridgeshire] ; New York : Cambridge University Press, 1986)
"this book explores the areas of income distribution and welfare. Analyzing redistribution policies developed appropriate techniques to analyze the extent and nature of income inequality and welfare and to measure the direct impact of taxes and government cash transfers on the distribution of income by size of income and other household characteristics. What was the extent of inequality of income and which way was it moving? Was the burden of taxation evenly distributed across the population? Did the rich pay proportionately more or less taxes than the poor? What were the effects of government programs on the welfare of particular groups in the community? An attempt was made to answer these and other related questions by an analysis of the Australia data obtained from the 1975-1976 Household Expenditure Survey. Written in a fairly nontechnical manner, Analyzing redistribution policies can be understood with limited knowledge of economics and statistics."--Cover.
Machine derived contents note: Preface -- 1. Introduction -- Part I. Conceptual Issues in the measurement of Income Distribution: 2. Income-recipient units and their differing needs -- 3. Income concept in the analysis of income distribution -- Part II. Measures of Income Inequality, Redistribution, and Equity: 4. On the measurement of income inequality -- 5. Measures of redistribution and equity -- Part III. Distribution and Redistribution of Income: 6. Distribution of income in Australia -- 7. Tax rates and government benefit rates by income ranges -- 8. Effects of taxes and cash benefits on equity -- 9. Redistribution of income within and between socioeconomic and demographic groups -- 10. progressivity of sales tax on individual expenditure items -- Part IV. Welfare and Poverty: 11. Distribution of welfare in Australia -- 12. Optimal negative income taxation, when individuals feel envious -- 13. The impact of taxes and cash benefits on poverty -- Appendix -- Notes -- References -- Author index -- Subject index.
Includes indexes.
Bibliography: p. 275-287.
Keywords: Income distribution -- Government policy -- Australia; Progressive taxation -- Australia; Transfer payments -- Australia; Income distribution; Australia -- Social conditions; Income -- Redistribution